2009
DOI: 10.1016/j.jesp.2008.09.012
|View full text |Cite
|
Sign up to set email alerts
|

The intergenerational transmission of implicit and explicit attitudes toward smoking: Predicting adolescent smoking initiation

Abstract: This study examined the intergenerational transmission of implicit and explicit attitudes toward smoking, as well as the role of these attitudes in adolescents' smoking initiation. There was evidence of intergenerational transmission of implicit attitudes. Mothers who had more positive implicit attitudes had children with more positive implicit attitudes. In turn, these positive implicit attitudes of adolescents predicted their smoking initiation 18-months later. Moreover, these effects were obtained above and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 61 publications
(81 reference statements)
1
67
1
Order By: Relevance
“…Prior studies have found that smokers are less negative than nonsmokers in both implicit and explicit attitudes ( Huijding, de Jong, Wiers, & Verkooijen, 2005 ;Sherman, Rose, Koch, Presson, & Chassin, 2003 ;Swanson, Rudman, & Greenwald, 2001 ). Data from our laboratory have shown that implicit attitudes toward smoking prospectively predicted both smoking initiation among adolescents ( Sherman, Chassin, Presson, Seo & Macy, 2009 ) and smoking cessation among adults ( Chassin, Presson, Sherman, Seo, & Macy, 2010 ). These studies and the current study measured implicit attitudes toward smoking with the Implicit Association Test (IAT; Greenwald, McGhee, & Schwartz, 1998 ).…”
Section: Implicit and Explicit Attitudes And Tobacco Controlmentioning
confidence: 65%
“…Prior studies have found that smokers are less negative than nonsmokers in both implicit and explicit attitudes ( Huijding, de Jong, Wiers, & Verkooijen, 2005 ;Sherman, Rose, Koch, Presson, & Chassin, 2003 ;Swanson, Rudman, & Greenwald, 2001 ). Data from our laboratory have shown that implicit attitudes toward smoking prospectively predicted both smoking initiation among adolescents ( Sherman, Chassin, Presson, Seo & Macy, 2009 ) and smoking cessation among adults ( Chassin, Presson, Sherman, Seo, & Macy, 2010 ). These studies and the current study measured implicit attitudes toward smoking with the Implicit Association Test (IAT; Greenwald, McGhee, & Schwartz, 1998 ).…”
Section: Implicit and Explicit Attitudes And Tobacco Controlmentioning
confidence: 65%
“…To the best of our knowledge, however, only two attempts have been undertaken to investigate the relationship between smoking in adolescents and automatic parental cognitions about smoking. A cross-sectional (Chassin et al, 2002) and a longitudinal study (Sherman et al, 2009) have shown that parents' implicit cognitions about general smoking are related to their offspring's smoking behavior. Sherman et al (2009) observed that the degree to which mothers had a positive implicit attitude toward smoking was predictive of smoking initiation in their offspring 18 months later, via adolescents' positive implicit attitudes about smoking.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional (Chassin et al, 2002) and a longitudinal study (Sherman et al, 2009) have shown that parents' implicit cognitions about general smoking are related to their offspring's smoking behavior. Sherman et al (2009) observed that the degree to which mothers had a positive implicit attitude toward smoking was predictive of smoking initiation in their offspring 18 months later, via adolescents' positive implicit attitudes about smoking. These studies underscore the added value of taking into account implicit parental cognitions when trying to predict substance use in adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations